2019
DOI: 10.3390/nu11071683
|View full text |Cite
|
Sign up to set email alerts
|

Acute Supplementation with Nitrate-Rich Beetroot Juice Causes a Greater Increase in Plasma Nitrite and Reduction in Blood Pressure of Older Compared to Younger Adults

Abstract: Nitrate-rich beetroot juice supplementation has been shown to improve cardiovascular and cognitive function in younger and older adults via increased nitric oxide production. However, it is unclear whether the level of effects differs between the two groups. We hypothesized that acute supplementation with nitrate-rich beetroot juice would improve cardiovascular and cognitive function in older and younger adults, with the potential for greater improvements in older adults. Thirteen younger (18–30 years) and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
3
39
1
Order By: Relevance
“…Beetroot is known for its antioxidant activities and widely used as a remedy for a variety of ailments including cardiovascular-related conditions, anemia, sexual weakness and bladder stones [2]. Some recent clinical studies have also indicated the usefulness of beetroot in managing blood pressure and cardiovascular health [3][4][5][6]. Beetroot has also gained popularity as a supplement to boost energy and improve performance in athletes [7][8][9][10].Interestingly, in the Traditional Persian Medicine practices, beetroot is one of the foods used in the prevention and managing of metastatic progression of cancer [11].…”
mentioning
confidence: 99%
“…Beetroot is known for its antioxidant activities and widely used as a remedy for a variety of ailments including cardiovascular-related conditions, anemia, sexual weakness and bladder stones [2]. Some recent clinical studies have also indicated the usefulness of beetroot in managing blood pressure and cardiovascular health [3][4][5][6]. Beetroot has also gained popularity as a supplement to boost energy and improve performance in athletes [7][8][9][10].Interestingly, in the Traditional Persian Medicine practices, beetroot is one of the foods used in the prevention and managing of metastatic progression of cancer [11].…”
mentioning
confidence: 99%
“…From a mechanistic perspective, we reason that the additive effects of nitric oxide - derived through chronic beetroot juice ingestion and repetitive shear stress invoked during resistance exercise training sessions (3 times per week for 8 weeks) [ 70 ] - will result in more robust endothelium-dependent vascular adaptations when compared to exercise training alone. Separately, dietary nitrate and habitual exercise training interventions have favorably influenced blood pressure [ 19 , [71] , [72] , [73] ], macrovascular [ 7 , 73 , 74 ], and microvascular function [ 75 ] in healthy older men and women. However, the cumulative effect of dietary nitrate coupled with exercise training has not yet been compared to exercise training alone, and it is further unknown whether such interventions will elicit differing adaptations in conduit or resistance vessels [ 63 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, acute supplementation with beetroot juice (source of dietary nitrate) causes a greater increase in plasma levels of nitrite in older compared with younger adults (Stanaway et al . 2019).…”
Section: Discussionmentioning
confidence: 99%